2014
DOI: 10.1121/1.4865196
|View full text |Cite
|
Sign up to set email alerts
|

The effects of rhythm and melody on auditory stream segregation

Abstract: 2Streaming by melody and rhythm AbstractWhilst many studies have assessed the efficacy of low-level similarity-based cues for auditory stream segregation, much less is known about whether and how the larger-scale structure of sound sequences support stream formation and the choice of sound organization. In two experiments, we investigated the effects of musical melody and rhythm on the segregation of two interleaved tone sequences. The two sets of tones fully overlapped in their pitch ranges, but differed from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 46 publications
(90 reference statements)
0
20
0
Order By: Relevance
“…For example, within a stochastic background, the spectrotemporal regularity of a repeating cluster of synchronous tones causes them to stream together into a perceptual object distinct from the acoustic background (Elhilali, Xiang, Shamma, & Simon, 2009; Elhilali, Ma, Micheyl, Oxenham, & A, 2010). Indeed, temporal regularity also aids temporal/sequential segregation by allowing listeners to predict upcoming sounds (Dowling et al, 1987; Bendixen et al, 2010; Devergie et al, 2010; Szalárdy et al, 2014). …”
Section: Introductionmentioning
confidence: 99%
“…For example, within a stochastic background, the spectrotemporal regularity of a repeating cluster of synchronous tones causes them to stream together into a perceptual object distinct from the acoustic background (Elhilali, Xiang, Shamma, & Simon, 2009; Elhilali, Ma, Micheyl, Oxenham, & A, 2010). Indeed, temporal regularity also aids temporal/sequential segregation by allowing listeners to predict upcoming sounds (Dowling et al, 1987; Bendixen et al, 2010; Devergie et al, 2010; Szalárdy et al, 2014). …”
Section: Introductionmentioning
confidence: 99%
“…Such a composite model would also better fit the variety of Gestalt principles governing the formation of perceptual objects. One issue that is common to almost all models reviewed here is that whereas previous research has shown that temporal regularity/predictability helps auditory stream segregation (e.g., Andreou et al, 2011; Rajendran et al, 2013; Szalárdy et al, 2014), present models do not explicitly handle the temporal structure of sound sequences. Thus future models should explore how more nuanced temporal features beyond simple presentation rate can be taken into account in modeling ASA.…”
Section: Summary and Future Directionsmentioning
confidence: 96%
“…Further, there is evidence that temporal coherence is indeed extracted in the human auditory system (O'Sullivan et al, 2015; Teki et al, 2016). However, in contrast to neural and Bayesian models, existing temporal-coherence models don't offer a clear path for capturing higher-order regularities within the sound input, which are known to help auditory stream segregation (Dowling, 1973; Bey and McAdams, 2002; Bendixen et al, 2010; Szalárdy et al, 2014). Further, by eliminating the formation of representations for alternative sound organizations, they do not account for multi-stable stimulus configurations.…”
Section: Summary and Future Directionsmentioning
confidence: 99%
See 1 more Smart Citation
“…They found that randomizing either or both tone sequences decreased the proportion of time listeners reported the A and B sequences to be perceived as separate streams (also see Bendixen et al, 2013). Szalardy et al (2014) constructed a pair of interleaved tone sequences using the notes of two different familiar melodies for each sequence. They similarly found that the proportion of time listeners reported a percept of streaming was less when the tones and/or their timing were scrambled than when the tones faithfully followed the melodies.…”
Section: Introductionmentioning
confidence: 99%